2016
DOI: 10.1371/journal.pone.0167627
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Jasmonic Acid Production by Lasiodiplodia theobromae Reveals Formation of Valuable Plant Secondary Metabolites

Abstract: Jasmonic acid is a plant hormone that can be produced by the fungus Lasiodiplodia theobromae via submerged fermentation. From a biotechnological perspective jasmonic acid is a valuable feedstock as its derivatives serve as important ingredients in different cosmetic products and in the future it may be used for pharmaceutical applications. The objective of this work was to improve the production of jasmonic acid by L. theobromae strain 2334. We observed that jasmonic acid formation is dependent on the culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Constitutive JA Signaling in jao2 Plants Depends on Higher Flux through the JAR1-COI1 Module 12OH-JA accumulation has been commonly observed in different organs and plant species (Miersch et al, 2008), and its importance is now being recognized for plant-microbe interactions. 12OH-JA and other JAs can be synthetized by some fungi (Eng et al, 2016), and a recent report suggested that fungus-produced 12OH-JA attenuates host immunity in rice (Patkar et al, 2015). We detected no 12OH-JA in the B. cinerea-infected aos mutant, which is devoid of any plantderived JA (L. Poirier and T. Heitz, unpublished result), indicating that this fungus does not produce 12OH-JA under our conditions.…”
Section: Jao2 Deficiency Activates Jasmonate Signaling In Unchallengementioning
confidence: 44%
“…Constitutive JA Signaling in jao2 Plants Depends on Higher Flux through the JAR1-COI1 Module 12OH-JA accumulation has been commonly observed in different organs and plant species (Miersch et al, 2008), and its importance is now being recognized for plant-microbe interactions. 12OH-JA and other JAs can be synthetized by some fungi (Eng et al, 2016), and a recent report suggested that fungus-produced 12OH-JA attenuates host immunity in rice (Patkar et al, 2015). We detected no 12OH-JA in the B. cinerea-infected aos mutant, which is devoid of any plantderived JA (L. Poirier and T. Heitz, unpublished result), indicating that this fungus does not produce 12OH-JA under our conditions.…”
Section: Jao2 Deficiency Activates Jasmonate Signaling In Unchallengementioning
confidence: 44%
“…We had considered Fg-cat as a candidate for the role of the “missing” AOS activity in fungi, in which case the adjacent 13 S -LOX gene in F. graminearum could provide the appropriate AOS substrate, as suggested as a potential role for the F. oxysporum 13 S -LOX homologue [15]). Many fungi including Fusarium species synthesize jasmonates [4548] (although we find no evidence concerning F. graminearum ). Notwithstanding the apparent logic, in the course of our extensive analyses we found no evidence of allene oxide synthesis nor cyclopentenone formation from interaction of Fg-cat with either 13 S -HPODE or 13 S -HPOTE, likely dismissing the possibility of its involvement in jasmonate synthesis in F. graminearum .…”
Section: Discussionmentioning
confidence: 67%
“…theobromae and members of the Fusarium family remain prototypes for studies of (+)-JA biosynthesis. L. theobromae (strain 2334) can routinely produce 300-500 mg (+)-JA per liter of growth medium and occasionally much more (17)(18)(19). In the fields, L. theobromae causes excessive growth of tropical fruit trees, possibly due to (+)-JA secretion (15,18).…”
mentioning
confidence: 99%
“…L. theobromae (strain 2334) can routinely produce 300-500 mg (+)-JA per liter of growth medium and occasionally much more (17)(18)(19). In the fields, L. theobromae causes excessive growth of tropical fruit trees, possibly due to (+)-JA secretion (15,18). Several subspecies of F. oxysporum, which infect garden stock, cabbage, and tulips, are also known to produce (+)-JA, 9,10-dihydro-JA, and their conjugates with isoleucine (15,20).…”
mentioning
confidence: 99%